2021
DOI: 10.3390/ph14050389
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Modelling Identifies and Addresses the Risks of Empiric Concentration-Guided Sorafenib Dosing

Abstract: The primary objective of this study is to evaluate the capacity of concentration-guided sorafenib dosing protocols to increase the proportion of patients that achieve a sorafenib maximal concentration (Cmax) within the range 4.78 to 5.78 μg/mL. A full physiologically based pharmacokinetic model was built and validated using Simcyp® (version 19.1). The model was used to simulate sorafenib exposure in 1000 Sim-Cancer subjects over 14 days. The capacity of concentration-guided sorafenib dose adjustment, with/with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…PBPK modelling and simulation is an established tool to support drug discovery and development and is a core element of the regulatory approval process in many jurisdictions [18]. Recent studies have further demonstrated the potential role of PBPK in predicting covariates affecting variability in drug exposure resulting from differences in patient characteristics [14,15,45], giving rise to the intriguing potential for this platform to support model-informed precision dosing [46,47]. This model provides an important foundation for establishing a PK/PD relationship for epirubicin; however, further work on population-based dose predictive modelling is imperative to inform optimal therapeutic windows for individualized dosage.…”
Section: Discussionmentioning
confidence: 99%
“…PBPK modelling and simulation is an established tool to support drug discovery and development and is a core element of the regulatory approval process in many jurisdictions [18]. Recent studies have further demonstrated the potential role of PBPK in predicting covariates affecting variability in drug exposure resulting from differences in patient characteristics [14,15,45], giving rise to the intriguing potential for this platform to support model-informed precision dosing [46,47]. This model provides an important foundation for establishing a PK/PD relationship for epirubicin; however, further work on population-based dose predictive modelling is imperative to inform optimal therapeutic windows for individualized dosage.…”
Section: Discussionmentioning
confidence: 99%
“…The core principle underlying precision dosing involves the comprehensive consideration of inter and intraindividual variability factors, encompassing genetic polymorphism, age, weight, organ function, and concurrent medication usage. 13,14 By methodically incorporating these influential variables, precision dosing strategies strive to optimize drug administration, tailored to the distinctive characteristics of individual patients, thereby enhancing the efficacy and safety of treatment interventions. 14 The last decade has witnessed a remarkable societal transformation driven by technological advancements.…”
Section: Introductionmentioning
confidence: 99%
“…Inconsistencies in treatment efficacy and tolerability may be attributed to variability in sorafenib exposure over time. Ruanglertboon et al developed a concentration-guided sorafenib dosing protocol to increase the proportion of patients that achieve a sorafenib C max within the required range by using a model to simulate sorafenib exposure [8].…”
mentioning
confidence: 99%